Modalités plurielles de l'action institutionnelle et implications sur l'activité enseignante. La dynamique des dispositifs et des agencements - Diane Rufin (Nantes Université, 2022)
Taking place in primary education in Geneva, using a study of official speeches and an ethnographic research, the article shows the plural modalities of institutional action - by mobilizing the concept of "device" declined in the plural and in the singular - and their implications on teaching activity - by considering the complex "agencements" that give them substance. In the first part, "les devices" reveal specific entities and functions as operational modes, and the permanent change as a residual device. They reorganize the activity, but the effects remain contrasted, according to local configurations and personalities. In the second part, "the device" appears hybrid, bringing together in an apparent coherence disparate modalities (principles, "modes of action" and regulations) which configure the activity in a paradoxical way. "Le dispositif" risks to escape everyone.